-2x-3=2x+9

Simple and best practice solution for -2x-3=2x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-3=2x+9 equation:


Simplifying
-2x + -3 = 2x + 9

Reorder the terms:
-3 + -2x = 2x + 9

Reorder the terms:
-3 + -2x = 9 + 2x

Solving
-3 + -2x = 9 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-3 + -2x + -2x = 9 + 2x + -2x

Combine like terms: -2x + -2x = -4x
-3 + -4x = 9 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + -4x = 9 + 0
-3 + -4x = 9

Add '3' to each side of the equation.
-3 + 3 + -4x = 9 + 3

Combine like terms: -3 + 3 = 0
0 + -4x = 9 + 3
-4x = 9 + 3

Combine like terms: 9 + 3 = 12
-4x = 12

Divide each side by '-4'.
x = -3

Simplifying
x = -3

See similar equations:

| 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= | | 2j-12=2 | | -5.7=1.9+1.9z | | 4n-3=29+8n | | 2x-52=88 | | 8x-11+15x+3x+9=180 | | -5x-4(-x-17)=76 | | y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 | | y+4=4(x+7) | | -7y-7=-5(y+5) |

Equations solver categories